Recycling and Reusing Polyethylene Waste as Antistatic and Electromagnetic Interference Shielding Materials - Mostafizur Rahaman; Ibrahim Abdullah Al Ghufais; Govindasami Periyasami; Ali Aldalbahi (International Journal of Polymer Science)
The aim of this work is to manage the waste product based on polyethylene (PE) films by recycling and reusing it as antistatic material for electronic packaging and electromagnetic interference (EMI) shielding material for protecting electronic equipment from interference of EM radiation. To achieve this, a conductive carbon black has been mixed with the PE waste at different weight percent values by ultrasonication via a solution mixing process. Mixing time for sonication was determined by ultraviolet-visible (UV-VIS) spectra. A differential scanning calorimetry (DSC) study showed that the low-density polyethylene (LDPE) and linear low-density polyethylene (LLDPE) are immiscible in their blend composition. The tensile properties of PE have reduced substantially after reprocessing. However, the addition of carbon black has improved its strength up to a certain loading. The electrical percolation threshold values, calculated using the classical power law and sigmoidal Boltzmann model, were obtained at 3.5 and 2.8 wt% loading of carbon black, respectively. The conductivity result revealed that 1-2 wt% carbon-loaded composites can be used as antistatic material. The composites, having carbon loading above 4 wt%, can be effective materials for EMI shielding application. The 10 wt% carbon-loaded composite exhibits EMI SE value 33 dB which means there is approximately 99.93% protection of EM radiation at the sample thickness of 1.0 mm. Moreover, FTIR analysis, thermal stability, AC conductivity, dielectric properties, permeability, and current-voltage characteristics are also discussed in detail. There is a substantial increment in thermal stability, and dielectric properties are observed with the addition carbon black loading within the polymer matrix.